Aggregative adherence of Klebsiella pneumoniae to human intestine-407 cells. - Favre-Bonte, S (1995)
Aggregative adhesion of Klebsiella pneumoniae LM3 to Intestine-407 (Int-407) cells was studied. Adhesive capacities were affected by the bacterial growth phase (with a maximum of adherence obtained during the exponential phase), temperature, multiplicity of infection, and length of incubation with Int-407 cells. Adhesion occurred through a cytochalasin D-sensitive process and was greatly reduced after treatment of Int-407 with cycloheximide, indicating that aggregative adhesion requires active participation of Int-407 cells. Transmission electron microscopy revealed that adherent bacteria were surrounded by a capsule-like material, apparently involved in both bacterium-Int-407 cell and bacterium-bacterium adherence. Examination with a scanning electron microscope showed interactions of intestinal cell microvilli with bacteria and formation in 3 h of a fibrous network within and around the bacterial clusters. We speculate that aggregative adhesion of K. pneumoniae mediated by a capsule-like extracellular material might explain the persistence of these strains inside the host gastrointestinal tract.